Measuring Brain Tumor Growth: Combined Bioluminescence Imaging–Magnetic Resonance Imaging Strategy - Sarah C. Jost; Lynne Collins; Sarah Travers; David Piwnica-Worms; Joel R. Garbow (Molecular Imaging)
Small-animal tumor models are essential for developing translational therapeutic strategies in oncology research, with imaging having an increasingly important role. Magnetic resonance imaging (MRI) offers tumor localization, volumetric measurement, and the potential for advanced physiologic imaging but is less well suited to high-throughput studies and has limited capacity to assess early tumor growth. Bioluminescence imaging (BLI) identifies tumors early, monitors tumor growth, and efficiently measures response to therapeutic intervention. Generally, BLI signals have been found to correlate well with magnetic resonance measurements of tumor volume. However, in our studies of small-animal models of malignant brain tumors, we have observed specific instances in which BLI data do not correlate with corresponding MRIs. These observations led us to hypothesize that use of BLI and MRI together, rather than in isolation, would allow more effective and efficient measures of tumor growth in preclinical studies. Herein we describe combining BLI and MRI studies to characterize tumor growth in a mouse model of glioblastoma. The results led us to suggest a cost-effective, multimodality strategy for selecting cohorts of animals with similar tumor growth patterns that improves the accuracy of longitudinal in vivo measurements of tumor growth and treatment response in preclinical therapeutic studies.